Membrane Fouling in Algal Separation Processes: A Review of Influencing Factors and Mechanisms - Novoa, Andres Felipe; Vrouwenvelder, Johannes S.; Fortunato, Luca (Frontiers in Chemical Engineering, 2021)
The use of algal biotechnologies in the production of biofuels, food, and valuable products has gained momentum in recent years owing to its distinctive rapid growth and compatibility to be coupled to wastewater treatment in membrane photobioreactors (MPBRs). However, membrane fouling is considered a main drawback that offsets the benefits of algal applications, by heavily impacting the operation cost. Several fouling control strategies have been proposed, addressing aspects related to characteristics in the feed water and membranes, operational conditions, and biomass properties. However, the lack of understanding of the mechanisms behind algal biofouling and control, challenges the development of cost-effective strategies needed for the long-term operation of MPBRs. This paper, reviews the progress on algal membrane fouling and control strategies. Herein, we summarize information in the composition and characteristics of algal foulants, namely algal organic matter (AOM), cells, and transparent exopolymer particles (TEP); and review their dynamic responses to modifications in the feedwater, membrane surface, hydrodynamics, and cleaning methods. This review comparatively analyses (i) efficiency in fouling control or mitigation, (ii) advantages and drawbacks, (iii) technological performance, and (iv) challenges and knowledge gaps. Ultimately, the article provides a primary reference of algal biofouling in membrane-based applications.